Effect of canopy-air interface roughness on HF-VHF wave propagation in forest. - Sarabandi, K.
The problem of electromagnetic wave propagation in a realistic forest environment in the high-frequency and very high-frequency bands is considered. In particular, the effect of the nonplanar interface between the air and the canopy, which has been ignored in previous models, is examined. An analytical formulation is obtained for the mean field when both the transmitter and the receiver are within the foliage. This formulation is based on distorted Born approximation and accounts for the surface roughness that exists between the canopy and air interface. It is shown that the surface roughness attenuates the so-called lateral wave slightly, which is the dominant source of the field at receiver locations far from the transmitter. It is also shown that this attenuation rate increases when the RMS height of the surface roughness is increased
Keywords: HF wave propagation; VHF wave propagation; Distorted Born approximation; Electromagnetic wave propagation; Forest canopy-air interface roughness; Lateral wave attenuation; Mean field; Nonplanar interface; Scattering; Surface roughness